2022
DOI: 10.1111/pan.14446
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Newborn Infant Parasympathetic Evaluation (NIPE™) index to changes in heart rate to detect intraoperative nociceptive stimuli in healthy and critically ill children below 2 years: An observational study

Abstract: Background: The validity of current tools for intraoperative objective assessment of nociception/antinociception balance during anesthesia in young and very young surgery children is unknown. Aim: Primary aim of the study was to test the hypothesis that the Newborn Infant Parasympathetic Evaluation (NIPE) index performs better in indicating nociception in anesthetized children below 2 years than changes in heart rate. Secondary aims were to evaluate associations between intraoperative changes in NIPE index val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…However, other studies found no correlation with pain scores ( 45 , 46 ). Moreover, the reported diagnostic performance varied considerably between studies, with the AUC ranging from 0.56 to 0.93 ( 41 , 42 , 44 , 46 48 ). NIPE generally performed better in neonates with higher levels of pain compared with those with mild pain.…”
Section: Monitoring- and Response-biomarkersmentioning
confidence: 99%
“…However, other studies found no correlation with pain scores ( 45 , 46 ). Moreover, the reported diagnostic performance varied considerably between studies, with the AUC ranging from 0.56 to 0.93 ( 41 , 42 , 44 , 46 48 ). NIPE generally performed better in neonates with higher levels of pain compared with those with mild pain.…”
Section: Monitoring- and Response-biomarkersmentioning
confidence: 99%
“…More recently, a 15–30% decrease in NIPE values has shown a sensitivity of 92% and a specificity of 96% for nociception during venous puncture, surgical skin incision and intubation [ 39 ]. In 2-year-old children undergoing brief tetanic stimulations (5 s, 100 Hz, 10 to 60 mA), NIPE proportionally decreased from a baseline of 75 ± 10 to 48 ± 12 (60 mA), whereas heart rate changed minimally [ 40 ].…”
Section: Nociception Monitorsmentioning
confidence: 99%
“…Pain, as defined by the International Association for the Study of Pain, is dependent on an individual’s conscious experience (https://www.iasp-pain.org/publications/iasp-news/iasp-announces-revised-definition-of-pain/). Therefore, while nociception is a physiologic phenomenon that may be assessed objectively with NIPE and ANI, although seconds to minutes behind,10 pain is intrinsically subjective. In addition, intraoperative neuroendocrine responses may not necessarily be a function of nociception or predict postoperative pain.…”
Section: Advances In Monitoring or Advances In Carementioning
confidence: 99%